2018
DOI: 10.3389/fpsyg.2018.00504
|View full text |Cite
|
Sign up to set email alerts
|

Non-cognitive Characteristics of Gifted Students With Learning Disabilities: An In-depth Systematic Review

Abstract: Gifted students who also have learning disabilities (G/LD) are often overlooked when students are assessed either for giftedness or specific learning disabilities. The cognitive and non-cognitive characteristics of these G/LD students are habitually discussed only briefly alongside identification and intervention issues and, beyond that, the relevance of non-cognitive characteristics is often left unconsidered. Accordingly, this study aims to conduct an in-depth review of the non-cognitive characteristics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 85 publications
(197 reference statements)
0
36
0
2
Order By: Relevance
“…Moreover, it is important to note that the lack of training in giftedness by learning disabilities teachers means they are unaware of the existence of SGLD and therefore, are unable to identify the characteristics of such students and make the appropriate referrals. The reason for this is because in eh literature, SGLD is usually discussed in terms of giftedness (Alkhunaini, 2013;Beckmann & Minnaert, 2018). Despite some teachers claiming to have observed students who exhibit both giftedness and learning disabilities within their classrooms, the emphasis in the Saudi education system is placed on a deficit model; as demonstrated in this study, teachers generally focus on learning disabilities and solely address these.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, it is important to note that the lack of training in giftedness by learning disabilities teachers means they are unaware of the existence of SGLD and therefore, are unable to identify the characteristics of such students and make the appropriate referrals. The reason for this is because in eh literature, SGLD is usually discussed in terms of giftedness (Alkhunaini, 2013;Beckmann & Minnaert, 2018). Despite some teachers claiming to have observed students who exhibit both giftedness and learning disabilities within their classrooms, the emphasis in the Saudi education system is placed on a deficit model; as demonstrated in this study, teachers generally focus on learning disabilities and solely address these.…”
Section: Discussionmentioning
confidence: 95%
“…Duality in profiles of gifted students with SLD may extend to psychosocial factors. Beckmann and Minnaert (2018) conducted a systematic review of studies examining noncognitive or psychosocial characteristics among high ability students with SLD. Authors summarized 23 studies with various methodologies to find common characteristics among participants.…”
Section: Twice‐exceptionality and The School Psychologistmentioning
confidence: 99%
“…Numerous qualitative studies (e.g., Park et al, 2018; Rubenstein et al, 2015) have identified parents' continuous need to advocate due to educators not understanding twice‐exceptionality or focusing solely on their child's disability. Knowledge of twice‐exceptionality, both in and out of gifted education, is important to identify and provide twice‐exceptional students requisite educational and occupational opportunities. Note variability in psychosocial factors, such as motivation or educational engagement (Beckmann & Minnaert, 2018), may represent an undiagnosed twice‐exceptionality. For example, gifted students who also have an SLD may feel frustrated by the gap between their very high potential and their relatively average or below‐average academic achievement (Beckmann & Minnaert, 2018), unlike the typically developing student whose academic growth is progressing at a grade‐expected rate that is consistent with their ability or potential. Recognize and support strengths‐based approaches in our schools.…”
Section: Implications and Recommendations For Educational Policy And mentioning
confidence: 99%
See 1 more Smart Citation
“…Esta condición representa un tema actual de importancia en la investigación científica, pues su identificación e intervención se vuelve un reto dentro de las aulas. Se considera doblemente excepcionales a los sujetos que, por un lado, se localizan en un rango excepcional correspondiente a su alto potencial y habilidades cognitivas, académicas y creativas y, por otro lado, se ubican en un extremo inferior de excepcionalidad debido a la presencia de algún trastorno relacionado a su aprendizaje (Beckmann y Minnaert, 2018).…”
Section: Introductionunclassified